Evaluation of effectiveness of classical massage in spinal pain syndromes - literature review - Iwona Dybowska; Wojciech Garczyński (Kazimierz Wielki University, 2017)
Back pain are often found not only in the elderly, but also often occur in people younger and younger. There are all sorts of diseases, not only the spine but also the soft tissue, paraspinal muscles and their attachments, with a tendency to recurrence of pain. Formation of pain syndromes is associated with the pathology of intervertebral discs and joints of the spine. Prior to treatment in the first place need to understand the genesis of pain and its symptoms. It should also be considered co-morbid conditions in a test subject. Among the methods of treatment of pain syndromes stand out treatments in the field of physical therapy, physiotherapy, and additional elements, ie. Manual therapy and neurophysiological methods. Equally important is the patient education about the prevention of, or re-education on how to perform activities of daily living, which is the basis for the prevention of recurrence of the disease or its total elimination. The aim of the study was to determine the efficacy of classical massage spinal pain syndromes. The paper presents various forms of rehabilitation, but the main emphasis is on the assessment of the effectiveness of classical massage in selected disease entities. The studies found positive effects of massage on the human body, proving that it eliminates common back pain, and increases its mobility in all planes, which results in improving the quality of everyday life. However, the main emphasis is on the assessment of the effectiveness of classical massage in selected disease entities. The studies found positive effects of massage on the human body, proving that it eliminates common back pain, and increases its mobility in all planes, which results in improving the quality of everyday life. However, the main emphasis is on the assessment of the effectiveness of classical massage in selected disease entities. The studies found positive effects of massage on the human body, proving that it eliminates common back pain, and increases its mobility in all planes, which results in improving the quality of everyday life.